4 x + 3 Y = 17
3 x - 4 Y + 6= 7
PLEASE SOLVE ONLY MY CROSS MULTIPLICATION METHOD
Answers
Answered by
0
Given System of equations is :
4x + 3y - 17 = 0 ------ (1)
3x - 4y + 6 - 7 = 0
3x - 4y - 1 = 0 ------ (2)
Compare the above equations with a1x + b1y + c1 = 0 and a2x + b2y + c2 = 0,
a1 = 4, b1 = 3, c1 = -17
a2 = 3, b2 = -4, c2 = -1
Now,
![\frac{x}{b1c2 - b2c1} = \frac{-y}{a1c2- a2c1} = \frac{1}{a1b2 - a2b1} \frac{x}{b1c2 - b2c1} = \frac{-y}{a1c2- a2c1} = \frac{1}{a1b2 - a2b1}](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%7D%7Bb1c2+-+b2c1%7D+%3D++%5Cfrac%7B-y%7D%7Ba1c2-+a2c1%7D+%3D++%5Cfrac%7B1%7D%7Ba1b2+-+a2b1%7D++)
![= \ \textgreater \ \frac{x}{3(-1) - (-4)(-17)} = \frac{-y}{(4)(-1) - (3)(-17)} = \frac{1}{(4)(-4) - (3)(3)} = \ \textgreater \ \frac{x}{3(-1) - (-4)(-17)} = \frac{-y}{(4)(-1) - (3)(-17)} = \frac{1}{(4)(-4) - (3)(3)}](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+++%5Cfrac%7Bx%7D%7B3%28-1%29+-+%28-4%29%28-17%29%7D+%3D++%5Cfrac%7B-y%7D%7B%284%29%28-1%29+-+%283%29%28-17%29%7D+%3D++%5Cfrac%7B1%7D%7B%284%29%28-4%29+-+%283%29%283%29%7D+)
![= \ \textgreater \ \frac{x}{-71} = \frac{-y}{47} = \frac{1}{-25} = \ \textgreater \ \frac{x}{-71} = \frac{-y}{47} = \frac{1}{-25}](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+++%5Cfrac%7Bx%7D%7B-71%7D+%3D++%5Cfrac%7B-y%7D%7B47%7D+%3D++%5Cfrac%7B1%7D%7B-25%7D+)
![= \ \textgreater \ \frac{x}{-71} = \frac{1}{-25} = \ \textgreater \ \frac{x}{-71} = \frac{1}{-25}](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+++%5Cfrac%7Bx%7D%7B-71%7D+%3D++%5Cfrac%7B1%7D%7B-25%7D+)
![x = \frac{71}{25} x = \frac{71}{25}](https://tex.z-dn.net/?f=x+%3D++%5Cfrac%7B71%7D%7B25%7D+)
![= \ \textgreater \ \frac{-y}{47} = \frac{-1}{25} = \ \textgreater \ \frac{-y}{47} = \frac{-1}{25}](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+++%5Cfrac%7B-y%7D%7B47%7D+%3D++%5Cfrac%7B-1%7D%7B25%7D+)
![= \ \textgreater \ y = \frac{47}{25} = \ \textgreater \ y = \frac{47}{25}](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C++y+%3D++%5Cfrac%7B47%7D%7B25%7D+)
Therefore x = 71/25, y = 47/25.
Hope this helps!
4x + 3y - 17 = 0 ------ (1)
3x - 4y + 6 - 7 = 0
3x - 4y - 1 = 0 ------ (2)
Compare the above equations with a1x + b1y + c1 = 0 and a2x + b2y + c2 = 0,
a1 = 4, b1 = 3, c1 = -17
a2 = 3, b2 = -4, c2 = -1
Now,
Therefore x = 71/25, y = 47/25.
Hope this helps!
siddhartharao77:
:-)
Similar questions